A lesson before dying zwischen Leben und Tod - Gaines, Ernest J. 1933-2019 (mediacs AG, 2003)
A frustrated teacher in a southern town, whose education is being underutilized, finds his own purpose in helping bring meaning to the last days of a young man due to be executed. In teaching one person to die with dignity, he redeems himself
Original: USA, 1999
Keywords: Feature films; Films for the hearing impaired; African American men / Louisiana / Drama; Death row inmates / Louisiana / Drama; Friendship / Louisiana / Drama; Louisiana / Race relations / Drama; Film; DVD-Video